Improving Children's Vocabulary Through E-Comic Media: A Development in Early Childhood Education - Lestari, Titik; Delfi Eliza; Farida Mayar; Dadan Suryana (Institut Agama Islam Negeri Madura, 2025)
Conventional learning results in low mastery of early childhood skills, so the use of digital media is necessary in the learning process. This research aims to develop and test the validity, practicality, and effectiveness of digital-based learning media in the form of e-comics at Kindergarten. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Validation was conducted by three experts, and the trial subjects were students at Pembina II State Kindergarten, Batam City. Data collection was conducted through validation, practicality, and effectiveness questionnaires, and then analyzed descriptively quantitatively. The research results indicate that the developed e-comic media is highly suitable for use, with validation results from subject matter experts at 100%, language experts at 90.4%, and media experts at 90%. The response from educators and students towards this media is also very positive. The practicality test obtained a percentage of 88.6% (very practical category), while the effectiveness test showed a figure of 88.75% (very effective category). Thus, the developed e-comic has proven to be valid, practical, and effective in enhancing the vocabulary of early childhood children and is suitable for use as a learning medium in kindergartens.